Executive burnout : eastern and western concepts, models, and approaches for mitigation - Sharma, Radha R.; Cooper, Cary L.,
Never before has the world witnessed the phenomenon of severe stress and burnout on such a large scale as in recent years. Globalization, technological advances and economic meltdown have brought about a plethora of unprecedented challenges for industry and organizations across the globe. Consequently, executives have been under growing stress due to economic uncertainties, mergers and acquisitions, role erosion and restructuring, resulting in increased workloads, longer hours and demands for greater productivity and efficiency. This changing environment has created job insecurity, anxiety, dissatisfaction and emotional exhaustion causing a rapid increase in executive burnout. This book provides the most comprehensive analysis of the construct of burnout, including its magnitude, a global research review, a typology of models, comparisons between professions and consequences of burnout for individuals and organizations. In addition, it provides the views of mental health professionals, empirically derived causes, symptoms and coping techniques, while throwing light on preventative measures and comparing Eastern and Western approaches to mitigate the effects of burnout.